Factors that Influence the Application of the Concept of New Green Areas in Residential Areas Using Structural Equation Modeling-Part Least Square (SEM-PLS) - Amalia, Nur; Husin, Albert Eddy; Prastowo, Ferdiansyah Ibnu (ASTONJADRO, 2023)
Climate change and global warming or environmental damage and degradation have led to various natural disasters, social disasters and serious economic disasters. Global warming has increasingly affected not only our daily lives but also our business activities. Housing and settlements are one of the basic human needs that must be met to be able to live decently. However, human life and its business activities have not paid enough attention to environmental issues. Excessive exploitation of non-renewable energy beyond normal limits is also damaging to the environment. The application of the new green area concept is a consequence of the increase in the cost of green areas incurred by stakeholders so that residential areas become environmentally friendly, the concept of new green areas, Value Engineering (VE), Life Cycle Cost Analysis (LCCA) are the main factors that influence the improvement of cost performance of implementing the concept new green areas in residential areas in Indonesia, using structural equation model- partial least square (SEM-PLS) analysis. This research has an update related to the concept of applying new green areas to residential areas in Indonesia. The results of this study obtained "10 factors that affect the cost performance of new green areas in residential areas", namely Project Management, Infrastructure and Facilities Burdens, Infrastructure and Facilities Service Functions, Microclimate and Ecosystem Preservation, Environmentally Friendly Materials, Development, Cost Breakdown Structure, LCC Analysis, Evaluation, Value Engineering.